2017
DOI: 10.28992/ijsam.v1i1.23
|View full text |Cite
|
Sign up to set email alerts
|

CSR Disclosures in the Mining Industry: Empirical Evidence from Listed Mining Firms in Indonesia

Abstract: Abstract:Companies that are involved in CSR strive to meet the expectations of stakeholders. Therefore, CSR and CSR reporting are tools of legitimacy to demonstrate its obedience (legitimacy theory). This study aims to look at empirical evidence on the effect of profitability and environmental performance on CSR disclosure. This study examined the target population of mining companies listed on the Indonesian Stock Exchange that included the CSR reporting in the 2010-2014 annual report, obtained a sample of 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
16

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 18 publications
(38 reference statements)
1
44
0
16
Order By: Relevance
“…Asmeri et al (2017) showed that CSR and CSR reporting are tools of legitimacy for companies to demonstrate their obedience, also that environmental performance has effect on CSR disclosure.…”
Section: Resultsmentioning
confidence: 99%
“…Asmeri et al (2017) showed that CSR and CSR reporting are tools of legitimacy for companies to demonstrate their obedience, also that environmental performance has effect on CSR disclosure.…”
Section: Resultsmentioning
confidence: 99%
“…Khan et al () studied the extent of CSR disclosure in the annual reports in Bangladeshi and found that companies do so in order to achieve and retain legitimacy by disclosing companies' practices. In Indonesia, Asmeri et al () studied the CSR disclosure by mining companies listed on the Indonesia stock exchange for 2010–2014 and found that profitability did not influence disclosure whereas environmental performance had positive relationship with disclosure.…”
Section: Prior Literature and Justification Of The Studymentioning
confidence: 99%
“…Similarly, an allegation to CSR in developing countries is that it is only providing meagre amounts, which cannot help the recipient stakeholders to improve their conditions and lead to poverty reduction (Ite, ). The study of Asmeri et al () in Indonesia reported on the relationship of profits and environmental performance on CSR disclosure was relevant although it was concerned with mining sector alone. Other sectors of the economy are also worth studying in order to provide a view in which CSR activities are disclosed and preferably looking at other developing contexts.…”
Section: Prior Literature and Justification Of The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, GRI has outlined guidelines for preparing social reports or sustainability (Asmeri et al, 2017); . GRI develops reporting guidelines using a global consensus search process that involves both the company as the reported organization, and also the user of the report such as employees and investors (Galani et al, 2012).…”
Section: Introductionmentioning
confidence: 99%